ChemInform Abstract: Catalytic Enantioselective Mannich‐Type Reaction via a Chiral Silver Enolate. Issue 22 (3rd June 2014) - Yanagisawa, Akira; Lin, Yuqin; Miyake, Ryoji; Yoshida, Kazuhiro
Abstract All reaction products are isolated with 98% diastereoisomeric excess.